Frugal MOOCs: An Adaptable Contextualized Approach to MOOC Designs for Refugees - Shah, Mariam Aman; Santandreu Calonge, David (International Review of Research in Open and Distributed Learning, 2019)
There is a growing body of literature that recognizes the role Massive Open Online Courses (MOOCs) can play in improving access to education globally, and particularly to thousands of people in developing and developed countries. There is increasing concern, however, that the millions of displaced refugee learners throughout Europe, the Middle East, and other regions are still disadvantaged when it comes to engaging in learning through MOOCs. The reasons for this disadvantage range from a lack of appropriate infrastructure or other supporting structures, to a lack of contextualized content. So far, little attention has been paid to contextualized MOOC models, which may both impact policies and be adapted to the specific needs of these learners who often do not have the means to access many education opportunities. Therefore, the purpose of this paper is to propose a frugally-engineered MOOC model that addresses the barriers of access and participation for refugees. This paper engages in an exploratory research methodology, using findings from the literature and expert opinions gathered through interviews. These findings lead to the development of what the authors call a Frugal MOOC Model which can be contextualized to meet the needs of refugee learners. The paper goes on to highlight the development of the Frugal MOOC Model as the first phase of an ongoing study. It concludes with recommendations for the next phase of the study: how to implement the newly developed model.